Academic performance of UPV Iloilo High School students admitted under the democratized admission scheme - Apalacio, Reymund Diaz
As its contribution to the enhancement of the social welfare of people, especially the poor, in a poor developing country like the Philippines, a government university like UP has embarked on a policy democratized education which includes the scheme of democratized admission at the UPV Iloilo High School. This paper undertook action research, which is the applications of tools and methods of social science to immediate, practical problems, to determine the academic performance of economically poor students admitted under the new, democratized admission scheme of the UPV Iloilo High School. It was found out that generally they perform as well as their better-off counterparts under the old scheme (with tuition fees).